Total elemental composition of soils in Sub-Saharan Africa and relationship with soil forming factors - Towett, Erick K.; Shepherd, Keith D.; Tondoh, Jérôme E.; Winowiecki, Leigh Ann; Tamene, Lulseged D.; Nyambura, Mercy; Sila, Andrew M.; Vågen, Tor-Gunnar; Cadisch, Georg (Elsevier, 2015)
A thorough understanding of the variation in total soil element concentrations is important especially in the Sub-Saharan Africa (SSA) soil contexts for agricultural and environmental management at large scale. Fingerprinting of soil elemental composition may form a useful basis for evaluating soils in a way that relates to soil-forming factors and inherent soil functional properties. The objectives of this paper are to quantify the proportion of variability in total elemental composition by total X-ray fluorescence (TXRF) method of 1074 soil samples from the Africa Soil Information Service (AfSIS) Project baseline and to determine the relationships with soil forming factors. The samples were from 34 sentinel sites measuring 10 × 10 km, randomized within major climate zones in SSA. Within each sentinel site there were sixteen spatially stratified 1 km2 clusters, within which there were ten 100 m2 plots. The within and between site patterns of variation in total element composition of 17 elements; Al, P, K, Ca, Ti, V, Cr, Mn, Fe, Ni, Cu, Zn, Ga, Sr, Y, Ta, and Pb, were explored. Total element concentration values were within the range reported globally for soil Cr, Mn, Zn, Ni, V, Sr, and Y and higher than reported range for Al, Cu, Ta, Pb, and Ga. There were significant variations (P < 0.05) in total element composition within and between the sites for all the elements analyzed with the greatest proportion of total variance and number of significant variance components occurring at the site (55–88%) followed by the cluster nested within site (10–40%) levels. The explorations of the relationships between element composition data and site factors using Random Forest regression demonstrated that soil-forming factors have important influence on total elemental composition in the soil. The fact that the soil-forming factors are related to the concentration of naturally occurring elements in the soil gives rise to the notion that they might be predicted from the soils' element composition. Results implied that > 70% of variation in soil element composition patterns can be predicted using information in existing databases or readily observable features. Successful use of TXRF technique would open up possibilities for using total soil elemental composition fingerprints as a useful basis for characterizing soils in a way that relates to soil-forming factors and inherent soil functional properties.